Histidine-Proline Rich Glycoprotein (HPRG) binds and transduces anti-angiogenic signals through cell surface tropomyosin on endothelial cells - Guan, Xiaojun; Juarez, Jose C.; Qi, Xiaoping; Shipulina, Natalya V.; Shaw, David E.; Morgan, William T.; McCrae, Keith R.; Mazar, Andrew P.; Doñate, Fernando (Thrombosis and Haemostasis, 2004)
The anti-angiogenic properties of the histidine-proline–rich (H/P) domain of HPRG have recently been described (Juarez JC, et al. Cancer Research 2002; 62: 5344-50). However, the binding site that mediates these properties is unknown. HPRG is evolutionarily, functionally and structurally related to cleaved high molecular weight kininogen (HKa), an anti-angiogenic polypeptide that stimulates apoptosis of proliferating endothelial cells through binding to cell-surface tropomyosin (Zhang J-C, et al. Proc Natl Acad Sci USA 2002; 99: 12224-9). In this study, we demonstrate that HPRG binds with high affinity to FGF-2–stimulated human umbilical vein endothelial cells (HUVEC) and immobilized tropomyosin in a Zn2+ or pH-dependent manner, and that this interaction is mediated by the H/P domain of HPRG. At least two binding sites for HPRG, tropomyosin and heparan sulfate proteoglycans (HSPs), were identified on the surface of FGF-2–activated endothelial cells. Translocation of tropomyosin to the surface of HUVEC occurred in response to FGF-2, and the anti-angiogenic activity of HPRG in a Matrigel plug model was partially inhibited by soluble tropomyosin. These results suggest that HPRG binds to endothelial cell surface tropomyosin which at least partially mediates the antiangiogenic effects of HPRG.
Keywords: HPRG; angiogenenesis; endothelial cells; tropomyosin